Reducing the Production Lead Time of an Industry Using Value Stream Mapping Integrated with Kaizen - Bhat, Ritesh; Mohan, Nanjangud; Naidu, Mohindar; Shivamurthy, Shivakumar (International Journal of Engineering and Technology, 2018)
Lean manufacturing tools and techniques acts as a major industrial management driver in the modern world since they attracted the industrialist at an early period in its raw form. Value stream mapping is a lean tool that helps not only to identify the issues hindering the productivity in an industry but also helps to decide upon the right lean tool to be used for improving the same. This article focuses on the implementation of value stream mapping in one of the leading pharmaceutical company to assess the current productivity and recommending improvement. The recommended improvement through the future state map shows that the effective implementation of lean tools reduces the production lead-time by 60.29%.Â Â
Keywords: lean production; mapping; value stream mapping; industrial management; production lead-time; kaizen; work productivity